Nongeocentric axial dipole field behavior during the Mono Lake excursion. Issue 4 (2nd April 2014) - Negrini, Robert M.; McCuan, Daniel T.; Horton, Robert A.; Lopez, James D.; Cassata, William S.; Channell, James E. T.; Verosub, Kenneth L.; Knott, Jeffrey R.; Coe, Robert S.; Liddicoat, Joseph C.; Lund, Steven P.; Benson, Larry V.; et al.
Abstract A new record of the Mono Lake excursion (MLE) is reported from the Summer Lake Basin of Oregon, USA. Sediment magnetic properties indicate magnetite as the magnetization carrier and imply suitability of the sediments as accurate recorders of the magnetic field including relative paleointensity (RPI) variations. The magnitudes and phases of the declination, inclination, and RPI components of the new record correlate well with other coeval but lower resolution records from western North America including records from the Wilson Creek Formation exposed around Mono Lake. The virtual geomagnetic pole (VGP) path of the new record is similar to that from another high‐resolution record of the MLE from Ocean Drilling Program (ODP) Site 919 in the Irminger Basin between Iceland and Greenland but different from the VGP path for the Laschamp excursion (LE), including that found lower in the ODP‐919 core. Thus, the prominent excursion recorded at Mono Lake, California, is not the LE but rather one that is several thousands of years younger. The MLE VGP path contains clusters, the locations of which coincide with nonaxial dipole features found in the Holocene geomagnetic field. The clusters are occupied in the same time progression by VGPs from Summer Lake and the Irminger Basin, but the phase of occupation is offset, a behavior that suggests time‐transgressive decay and return of the principal field components at the beginning and end of the MLE, respectively, leaving the nonaxial dipole features associated with the clusters dominant during the excursion.